Răspuns:
a) x + y - z=7;
b)x+z-y = 10;
c) y + z-x=4
(x, y, z) i.p. (2,3,4)
x/ 1/2= y/ 1/3= z/ 1/4
2x = 3y = 4z
x= 3y/2
z= 3y/4
Inlocuim:
a) x + y - z=7
3y/2+ y+ 3y/4=7
Aducem la același numitor ,fiind 4:
6y/4+ 4y/4+ 3y/4= 28/4 /×4
13y =28
y=28/13
x= 3y/2
x= (3×28/13)/2
x= 84/26
x= 42/13
z= 3y/4
z= (3× 28/13)/4
z= 84/52
z= 21/13
x= 42/13
y= 28/13
z= 21/13
b)x+z-y = 10
x= 3y/2
z= 3y/4
Inlocuim :
3y/2+ 3y/4 - y=10
6y/4+ 3y/4- 4y/4= 40/4
5y/4=40/4 /×4
5y= 40 /:5
y= 8
x= 3y/2
x= (3×8) /2
x= 24/2
x = 12
z= 3y/4
z= (3×8)/4
z= 24/4
z= 6
x= 12
y= 8
z= 6
c) y + z-x=4
x= 3y/2
z= 3y/4
y+ 3y/4- 3y/2 = 16/4
4y/4+ 3y/4- 6y/2= 16/4
y/4 = 16/4 /×4
y= 16
x=3y/2
x= (3×16)/2
x= 48/2
x= 24
z= 3y/4
z= (3×16)/4
z= 48/4
z= 12
x= 24
y= 16
z= 12
Explicație pas cu pas: